KONFLIK DALAM PENGELOLAAN PARKIR LIAR DI PANTAI PURUS KELURAHAN RIMBO KALUANG KECAMATAN PADANG BARAT KOTA PADANG - AMRIL, ILMIATI - (Pendidikan Sosiologi, 2014)
The background of this research is the people who activity in the city do not understand about the area parkirng restrictions. So, they park their vehicle haphazardly and the parking attendant in the area just directing the legal fiction vehicle users to park their vehicle in the illegal parking area. This thesis is based on the formulation of the problem is how conflicts in the illegal parking management at Purus Beach Village Rimbo Kaluang District of West Padang, Padang City. The purpose of this paper is to describe the presence of illegal parking at Purus Beach, to describe the interest of the parties involved in the existance of illegal parking at Purus Beach Padang and then to describe the forms of a conflict and resolution related to illegal parking at Purus Beach.The study was conducted over two months on July and August 2014. The analysis in this study using the Dahrendorf conflict theory. The design of study is a qualitative research and descriptive analysis, sample was 17 informants who choose used purpossive sampling technique. The selection of an informants based on certain criteria. Data collection used observation and limited role technic, indept interviews and the study of documents.The results of the field study showed that illegal parking was occured at Purus Beach since a bridge was built in 2008, when the bridge opened in 2013 then at the time the people began to earn a living. Parking area that have not obtained permission from the authorities has been taken over by the chairman of the local youth. Challenges that occurred at the time, when the other side there are demands to the existence of the illegal parking. The reaction of the people as a parking service users who feel annoyed and forced to pay parking fees when they had just come. The was involved in the illegal parking is a parking attendant, the owner of the vehicle, youth leaders, community leaders and the Departement of Transportation Padang. This form of conflict that occured in the management of illegal parking were a conflict between illegal parking officer with the vehicle owner, where the owner of the vehicle lost their vesichel when parking, then conflicts between illegal parking attendants with parking unit in conducting enforcement. Conflict resolution between illegal parking officer with the vehicle owner by means of conciliation and conflict resolutions with UPT Perparkiran by pursuing a strategy of cooperation.